PENGARUH TOTAL QUALITY MANAGEMENT (TQM), BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN ISLAM TERHADAP KINERJA KARYAWAN PADA ASSALAAM HYPERMARKET KARTASURA - Widiyastuti, Artiningrum (El-Hayah, 2017)
Abstract : This research aims at determining the effect of Total Quality Management (TQM), organization culture and Islamic leadership style on employees’ performance of Assalam Hypermarket Kartasura in 2017 partially and simultaneously.This research applied quantitative method. Population of this research was 100 employees of Assalam Hypermarket Kartasura. Technique of collecting data used questionnaire given to 80 respondents. Data were analyzed by using test of requirement and hypothesis applying program of SPSS 17.0. The result of this research indicates that R2 of 0.253 is 25.3% variation of employee performance variable can be explained by variation of variable of  Total Quality Management (TQM), Organization Culture and Islamic Leadership Style. Meanwhile, 75% is variable that is not included in model similarity applied. The test partially shows positive and significant effect between variable of TQM and employees’ performance with significant value of t more or less 0,05 (0,003 more or less 0,05) and tobserved more than ttable i.e. 3,102 more than 1,990. Variable of Organization Culture shows positive and significant effect on employees’ performance with significant value of t more or less 0,05 (0,048 more or less 0,05) and tobserved more than ttabel  i.e. 1,855 more than 1,990. Meanwhile, variable of Islamic Leadership Style gives positive and significant effect on employees’ performance with significant value of t more or less 0,05 (0,002 more or less 0,05) and tobserved more than ttable i.e. 3,284 more than 1,990.Keywords: Total Quality Management (TQM), Organization Culture, Leadership Style, Employees’ performance